(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the features of the formation of immunity to "popular culture" among adolescent schoolchildren on the basis of a gender approach. It considers adolescence as a difficult, conflict period, and the development of self-awareness and self-esteem during this period.